2022
DOI: 10.1111/bdi.13174
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar II disorder: Once missed, now dismissed, time to resist

Abstract: The fewer the facts, the stronger the opinion.-Arnold H. Glasow.The work of science has nothing to do with consensus. Consensus is the business of politics. Science, on the other hand, requires only one investigator who happens to be right (with)…results that are verifiable by reference to the real world. -Michael Crighton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The essential controversy seems to be whether to use a dimensional or a categorical model of BD. Those who favor a dimensional model have argued that BP-II disorder has to be subsumed under the broader bipolar spectrum diagnosis[ 70 , 99 , 112 - 114 ], whereas others who favor a categorical approach maintain that there is sufficient evidence for an independent BP-II category[ 115 - 119 ]. The actual evidence in terms of validators provides almost equal support for both the dimensional and the categorical approaches.…”
Section: Summary Of the Changes Madementioning
confidence: 99%
“…The essential controversy seems to be whether to use a dimensional or a categorical model of BD. Those who favor a dimensional model have argued that BP-II disorder has to be subsumed under the broader bipolar spectrum diagnosis[ 70 , 99 , 112 - 114 ], whereas others who favor a categorical approach maintain that there is sufficient evidence for an independent BP-II category[ 115 - 119 ]. The actual evidence in terms of validators provides almost equal support for both the dimensional and the categorical approaches.…”
Section: Summary Of the Changes Madementioning
confidence: 99%
“…However, studies that recruited both patients with BD I and BD II found that psychotic symptoms were associated with a higher frequency of a first diagnosis different from BD or major depressive disorder (MDD), a prevalent manic polarity, and a higher number of lifetime manic episodes (more than six) [ 23 ]. Given that previous studies have frequently reported differences in clinicodemographic factors, including psychotic features between patients with BD I and BD II [ 24 , 25 ], it is possible that patients’ different types of diagnosis may contribute to the inconsistent results.…”
Section: Introductionmentioning
confidence: 99%